2013
DOI: 10.7287/peerj.preprints.56v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of RNA in exosomes secreted by human breast cancer cell lines using next-generation sequencing

Abstract: Exosomes are nanosized (30-100 nm) membrane vesicles secreted by most cell types. Exosomes have been found to contain various RNA species including miRNA, mRNA and long non-protein coding RNAs. A number of cancer cells produce elevated levels of exosomes. Because exosomes have been isolated from most body fluids they may provide a source for non-invasive cancer diagnostics. Transcriptome profiling that uses deep-sequencing technologies (RNA-Seq) offers enormous amount of data that can be used for biomarkers di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 0 publications
2
40
0
1
Order By: Relevance
“…Hierarchical clustering was conducted using Euclidean distance to cluster RNAs and samples. By standard detection criteria (13), 5,171 sRNAs, 1009 miRNAs and 13580 mRNAs with 1 RPKM in at least one sample were selected for analysis. Though paired t-test, 37 sRNAs, 204 miRNAs and 665 mRNAs were identified to have significant differential expression (p-value <0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Hierarchical clustering was conducted using Euclidean distance to cluster RNAs and samples. By standard detection criteria (13), 5,171 sRNAs, 1009 miRNAs and 13580 mRNAs with 1 RPKM in at least one sample were selected for analysis. Though paired t-test, 37 sRNAs, 204 miRNAs and 665 mRNAs were identified to have significant differential expression (p-value <0.05).…”
Section: Methodsmentioning
confidence: 99%
“…These nanoscaled extracellular vesicles are actively released by cells to transfer proteins, mRNA, and noncoding RNAs between cells. Interestingly, tumor cells release exosomes at a greater rate than normal cells, which suggests that they may play an important role in cancer . Some of the earliest exosome studies suggest that exosomes mediate B‐cell transformations .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 82 enriched GO categories were derived using a cut‐off of p < 0.05, including 56 biological process (BP), 19 cell component (CC) and seven molecular function (MF) categories (Table S2C) respectively. These categories were mainly focused on translational elongation, ribosome biogenesis, rRNA processing and rRNA metabolic process, clearly indicating that the exosomal RNAs were enriched in rRNA family species (Jenjaroenpun et al, ). Jenjaroenpun et al found that cellular exosomes contained various classes of RNA molecules with the major class represented by fragmented ribosomal RNA (rRNA), in particular 28S and 18S subunits.…”
Section: Resultsmentioning
confidence: 99%